A intolerância religiosa à brasileira: estudo de caso na cidade de Londrina / Paraná - Silva, Cláudia Neves da; Lanza, Fábio (Sociologia: Revista da Faculdade de Letras da Universidade do Porto, 2019)
The article discusses the permanence of intolerance and religious violence in Brazil, searching in documentary sources of the Catholic Church, commercial treaties and the Brazilian Constitutions information and data regarding the subject. Throughout history, forms of violence and intolerant practices of a religious nature remain and perpetuate themselves. The reports of religious intolerance reported in the media and the research data linked to the Laboratório de Estudos sobre Religiões e Religiosidades da Universidade Universidade Estadual de Londrina subsidized the construction of the analysis on the permanence of this intolerance and violence, highlighting the case of Yá Mukumby family, “Mãe de Santo” and leadership of the Movement Black in the city of Londrina, state of Paraná - south brazilian region. Despite the increase in legal frameworks that combat intolerance and religious violence, new strategies are still being developed and re-elaborated from the school environment and digital social networks.